(untitled) (Teaching and Learning Inquiry, 2017)
Clinical placements are central to physiotherapy students’ education, providing an environment in which students can apply learning they have been introduced to in academic settings. However placement learning has been identified as fraught with problems and resultant stress, and there is limited evidence available on what exactly makes a good placement for physiotherapy students. This paper reports on selected findings from a study exploring narratives of physiotherapy students over three years, relating to their overall experiences of being a student. A narrative prompt provided an opportunity for the students to speak about ‘episodes’ of their learning experiences. A number of these ‘episodes’ related to the students’ experiences of clinical placements; thus it was decided to extract these from the narratives and undertake a separate qualitative analysis of these placement experiences. The majority of the students reported positive experiences of placements overall; however, it was clear that some placement teams and mentors did not support students appropriately. A welcoming team and a mentor who facilitated learning from an individual student perspective were considered to be key to a good placement experience, whilst an unwelcoming team and a mentor who objectified the student resulted in bad placement experiences.